A cytidine deaminase-like protein modulates pyrimidine nucleotide homeostasis in Trypanosoma brucei - Ana Moro-Bulnes; Cristina Bosch-Navarrete; Pablo Antequera-Parrilla; Santiago Castanys; Antonio E. Vidal; Luis Miguel Ruiz-Pérez; Guiomar Pérez-Moreno; Dolores González-Pacanowska (Scientific Reports)
Abstract Pyrimidine nucleotide homeostasis is critical for DNA replication and cell viability, yet its regulation in Trypanosoma brucei, the causative agent of African trypanosomiasis, remains poorly understood. Here, we characterize a T. brucei cytidine deaminase-like protein (TbCDA-like), a kinetoplastid-specific enzyme absent in mammals, that harbors a deaminase domain and a zinc-finger CCCH motif. Using RNA interference (RNAi) and overexpression approaches, we demonstrate that TbCDA-like modulates pyrimidine nucleotide pools, influencing both ribonucleotide and deoxyribonucleotide profiles. Overexpression of TbCDA-like resulted in a substantial reduction of dCTP and CTP levels while elevating dTTP and UTP pools, suggesting a role in cytidine derivative deamination. Conversely, RNAi-mediated depletion of TbCDA-like caused CMP accumulation and reduced dTTP levels. Notably, overexpression induced severe cytotoxicity, growth arrest, DNA damage and cell cycle defects, evidenced by sub-G1 populations, increased nuclear H2A phosphorylation and aberrant kinetoplast and nuclear morphologies. Localization studies revealed that TbCDA-like is primarily cytosolic and relocalizes to stress granules upon nutrient deprivation, suggesting a role in RNA metabolism. These findings establish TbCDA-like as a key regulator of pyrimidine nucleotide homeostasis in T. brucei, linking nucleotide imbalances to DNA replication stress and genome instability. Given its absence in mammals, TbCDA-like presents an attractive target for therapeutic intervention against trypanosomiasis.